Klimawandel an öffentlichen Plätzen der Stadt Heidelberg. Transdisziplinäre Herausforderungen urbaner Räume. - Leutz, Kathrin (My University, 2019)
Hauptziel der Arbeit ist die Datenerhebung und Auswertung verschiedener Klimaparameter sowie die Befragung von PassantInnen zur Wahrnehmung des Klimawandels und der Gestaltung öffentlicher Räume in Heidelberg. Der Vergleich von Standorten in der historischen Altstadt mit neu geschaffenen Flächen ermöglicht es, die Schlüsselfaktoren der Stadtplanung zu bewerten, um sowohl klimatische als auch soziale Vorteile zu generieren. Daraus ergibt sich die Forschungsfrage: Welche Impulse können neue stadtklimatische Daten und Daten zur Wahrnehmung des Klimawandels an öffentlichen Plätzen der Stadt Heidelberg für die nachhaltige Stadtentwicklung geben? Der transdisziplinäre Ansatz basiert auf der Kombination verschiedener Methoden der Physischen sowie Human- und Sozialgeographie, der Einbeziehung von städtischen Akteuren und BürgerInnen sowie auf dem Konzept der forschungsorientierten Lehre. Aktuelle Problemstellungen der Stadtentwicklung werden in Zeiten des Klimawandels erlebbar gemacht und ermöglicht aktiv die Bearbeitung von Lösungs- und Anpassungsstrategien mitzugestalten. In Zusammenarbeit mit dem Umweltamt sollen aktuelle Fragen der städtebaulichen Anpassung an den Klimawandel transdisziplinär erforscht und außerdem für die weitere Informationsvermittlung aufbereitet werden. Die Auswertung des Gesamtdatensatzes zeigt aktuelle Tendenzen der Klimawandelentwicklung. Im Sommer 2018 weisen viele Teile der Stadt eine starke Erhitzung und Trockenheit auf. Maßnahmen, die regulierend auf das Mikroklima wirken, stehen im Co-Benefit mit den Wünschen der Befragten nach Beschattung, Begrünung, Diversität und einer generellen Verbesserung der Aufenthaltsqualität an öffentlichen Plätzen wie dem Universitätsplatz oder der Schwetzinger Terrasse.

"An old city like Heidelberg illustrates how its public space survives the renewal phases of its buildings and makes places permanently distinguishable. It is above all the built public space of a city that carries sustainability and identity in its structure - a goal to which Heidelberg feels particularly committed." (STADT HEIDELBERG 2005). The great challenge of climate change requires solutions, especially in cities, which are equally responsible for a large part of the anthropogenic greenhouse effect. Current questions on climate change adaptation have a high practical relevance for sustainable urban development on the one hand and for current scientific aspects on the other. Sustainable future models of the modern city primarily aim at reduction, with two essential factors: energy saving and energy efficiency. Increasing heavy precipitation and overheating events are examples that affect all fields of action of the city and require adaptation strategies. The main objective of this project is to collect data, evaluate various climate parameters and to survey citizens on their perception of climate change and the design of public spaces in Heidelberg. The comparison of locations in the historical old town with newly created areas makes it possible to evaluate the key factors of urban planning in order to generate both climatic and social benefits. Following on from this, the research question is: What impulses can new urban climate data and data on the perception of climate change in public places in Heidelberg provide for sustainable urban development? The transdisciplinary approach is based on the combination of different methods of physical as well as human and social geography, the involvement of urban actors and citizens and the concept of research-oriented teaching. The latter creates a learning environment in which students can experience the current problems of urban development in times of climate change and actively participate in the development of solution and adaptation strategies. In cooperation with the Environmental Office of the City of Heidelberg, current issues of urban development adaptation to climate change are to be researched transdisciplinarily and also prepared for teaching in teacher training. The evaluation of the overall data set shows current trends in climate change development. In the summer of 2018, many parts of the city exhibit severe heating and drought. Measures that have a regulating effect on the microclimate are in co-benefit with the respondents' wishes for shading, greening, diversity and a general improvement in the quality of life in public places such as the University square or the Schwetzinger Terrasse. These adaptation measures are essential from a scientific point of view.
Climate change in public places in the city of Heidelberg. Transdisciplinary challenges of urban spaces.
Keywords: Stadtplanung; Nachhaltige Stadtentwicklung; Stadtklima; Altstadt; Öffentlicher Raum; Platz; Klimawandel; Wahrnehmung; Befragung; Klimaanpassung; Stadtgestaltung; Umgestaltung; Aufenthaltsqualität; Beschattung; Begrünung; Klimadaten; Datenauswertung; Anpassungsstrategie; Maßnahmenkonzept